Modelling wave-seabed-pipe interaction through centrifuge experiment and a double-layered fluid model - Su, Siyang; Zhu, Jingshan; Kong, Deqiong; Li, Zhenyi; Zhu, Bin; Chen, Yunmin (Ocean engineering, 2025)
The response of seabed subject to wave loading and the corresponding impact on the stability of offshore geotechnical facilities have attracted worldwide research attention. This paper introduces a novel numerical analysis procedure, called the double-layered fluid (DLF) method, for the assessment of such problems. It combines the advantage of finite element analysis with sophisticated constitutive model and the moving boundary analysis considering the fluidic features of liquefied seabed soil. Validation is achieved through comparison with published numerical and experimental results, as well as a centrifuge test newly conducted by the authors. Following that, the capability of the DLF method in capturing the variation of wave characteristics during seabed liquefaction is demonstrated. A parametric study is presented to examine the development of excess pore pressure in the seabed around and away from a pipe, and the degradation effect on the bearing capacity. In the very loose or very dense sands, the uplift capacity of a pipe buried in the seabed reaches constant values during several couples of wave cycles, but keeps decreasing in the medium ones. The results demonstrate that the most vulnerable plane of pipe-soil interaction deviates from the upright direction and rotates towards the direction opposite to wave propagation. •A double-layered fluid analysis procedure is proposed for assessment of wave-induced response of seabed.•Centrifuge test is conducted using a newly developed centrifuge wave modelling device.•Development of excess pore pressure and corresponding impact on seabed bearing capacity is assessed.•Evolution of V-H failure envelops of pipe during wave loading is for the first time analysed.